CHALLENGES ENCOUNTERED BY EDUCATORS IN IMPARTING LAMPUNG LANGUAGE COURSES AS LOCAL CONTENT: A QUALITATIVE STUDY - Yustikasari, Miranda (LinguaScopes: International Journal of Language Education, 2024)
This study explores the challenges faced by educators in imparting Lampung language courses as local content, including lack of resources and limited support. This study is a qualitative study that utilize in-depth interviews and observations to gather data at YPT Pringsewu Vocational School, Indonesia. The research design focuses on exploring how incorporating Lampung vocabulary in education impacts students' cultural identity and academic performance. The findings suggest that educators also struggle with low student interest and motivation towards learning the Lampung language, highlighting the need for innovative teaching methods to make the course more engaging. Additionally, addressing societal attitudes towards the importance of preserving local languages might also be crucial in overcoming these challenges. Educators should work closely with community members and leaders to develop curriculum that is relevant and engaging, ensuring that the language is passed down to future generations in a meaningful way. Through collaboration and a holistic approach to language education, educators can help to ensure the longevity and vitality of the Lampung language. This can involve incorporating technology, interactive activities, and cultural immersion experiences into the curriculum. By making the learning process more dynamic and relevant to students' lives, educators can inspire a deeper appreciation for the language and motivate learners to actively participate in its preservation.